Rib fractures in blunt chest trauma - associated thoracic injuries - Iv. Dimitrov; Iv. Novakov; P. Bonev; A. Uchikov (Trakia Journal of Sciences)
PURPOSE. The aim of our retrospective study was to analyze the patterns of associated thoracic injuries in patients underwent blunt chest trauma and rib fractures. METHODS. The study included 212 patients with rib fractures due to blunt thoracic trauma. The mechanism of trauma, the type of rib fracture and the type of associated injuries were analyzed. RESULTS. The patients were divided in two groups according to the number of fractured ribs-group I included the patients with up to two fractured ribs (72 patients-33,9%), and group II – with ≥3 fractured ribs (140 patients-66,1%). Associated chest injuries were present in 36 of the patients from group I (50%), and in 133 patients from group II (95%). Pulmonary contusion was the most common intrathoracicinjurie-65,6% of the cases. The mean hospital stay was 8, 7 days. The lethality rate was 16,9% -all of them due to the associated chest injuries. CONCLUSIONS. The mortality related to rib fractures is affected by the associated thoracic injuries, the advanced age, and the number of fractured ribs.